(untitled) - Topolčány, Roman (Doprava a spoje, 2005)
The air accidents and incidents are here as long as aviation. Causes of accidents are coming already from production processes. But one of the biggest causes of air accidents is still staying here. A human. The human is working in production process, in air operation and in air control too. That are the hottest places, where the accident or incident can arise, and that places are connected with a human. This is for what a human have to be more careful and responsible.